Abuse of Authority in Dualism Perspective: Development of Corruption Crime Settlement Pattern - Suganda, Atma; Barus, Nenny Ekawaty (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is a criminal act that universally occurs in various countries in the world, including in Indonesia. Even if it cannot be said that Indonesia is more terrible than in other countries, corruption is a type of crime with a high degree of badness. So far the recipe for legal treatment of corruption in Indonesia is outlined through prevention and enforcement. This scientific work aims to explain the regulation of abuse of authority in relation to patterns of resolution of criminal acts of corruption. Conceptually this scientific work aims to provide thought suggestions in the context of the dimensions of preventing corruption. Basically this study is a normative legal research, because it methodologically uses a statutory approach with a descriptive-qualitative discussion approach. The results of the study found that the development of legal construction was related to the abuse of authority that shifted from the realm of criminal law to the state administrative law regime. The conclusion can be drawn that there is a development in legal politics in terms of solving corruption in accordance with the paradigm of progressive legal thinking. In the context of the dimensions of preventing criminal acts of corruption, it is necessary to strengthen broad regulations regarding areas prone to criminal acts of corruption and to be encouraged to prioritize the application of resolution to be more in the domain of state administrative law.